2019
DOI: 10.1111/1477-8947.12169
|View full text |Cite
|
Sign up to set email alerts
|

Are shocks to natural gas consumption transitory or permanent? A more powerful panel unit root test on the G7 countries

Abstract: This article re‐examines the persistence in natural gas consumption using an alternative methodology. We compare the results of traditional panel unit root tests with those provided by Bahmani‐Oskooee et al., which allow for both sharp and smooth breaks. Our analysis uses data for the G7 countries over the 1965–2016 years. The empirical findings show that while traditional unit root tests with sharp breaks lean towards the non‐stationarity of the series for all the G7 countries, modeling breaks in our unit roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Moreover, Aslan (2011) considered the stationarity of natural gas consumption in U.S states for the period 1960-2008 and concluded that natural gas consumption is stationary for 23 states. Cai and Magazzino (2019) probed the stationarity process of natural gas consumption for the period from 1965 to 2016 in G-7 countries using a Fourier transformed unit root test and found that the stationary process is valid for the majority of G-7 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Aslan (2011) considered the stationarity of natural gas consumption in U.S states for the period 1960-2008 and concluded that natural gas consumption is stationary for 23 states. Cai and Magazzino (2019) probed the stationarity process of natural gas consumption for the period from 1965 to 2016 in G-7 countries using a Fourier transformed unit root test and found that the stationary process is valid for the majority of G-7 countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first one, to study the underlying phenomena that leads to this non-stationarity; for example, Climate change have been documented as a permanent source of variation in prices, crop yields and demand of some assets ( Poveda and Álvarez, 2012 ; Zhiwei et al., 2018 ). On the other hand, the non-stationarity effect could be a subject of study due to its implications in policy and regulations; in housing prices, the non-stationarity prices of some household developments have led to some questions about sustainable development of those markets ( Cai and Magazzino, 2019 ; Mou et al., 2017 ). In the case of agri-products, speculation and arbitrage from intermediate brokers are elements to study, due to their impact to the sustainability of the colombian agricultural market.…”
Section: Description Of the Data And Empirical Resultsmentioning
confidence: 99%
“…Narayan et al (2008), Apergis and Payne (2010), Solarin and Lean (2016), Maslyuk and Smyth (2009) and Burakov (2019) investigated the stationarity of oil consumption and obtained mixed results. Regarding natural gas consumption, Aslan (2011), Golpe et al (2012), Shahbaz et al (2014b), Cai and Magazzino (2019) obtained contradictory findings in their studies, while Apergis et al (2010b), Abid and Alimi (2019) found that shocks are permanent in natural gas consumption. Moreover, Apergis et al (2010a) and Shahbaz et al (2014a) showed that shocks are transitory when Congregado et al (2012) revealed that the shocks on coal consumption are permanent.…”
Section: Literaturementioning
confidence: 94%